The Intelligence Board of INP and Foreign Journalists’ Supervision Issue in Indonesia - Syahputra, Alfin Reza; Rofii, Muhammad Syaroni (Interdisciplinary Social Studies, 2022)
Most likely, some illegal journalists have a mission or goal to seek information about intelligence activities that can damage Indonesia's image in the eyes of the world. Thus, it is necessary to supervise foreigners, especially foreign journalists. One of these supervisions is carried out by the National Police's Intelligence Board. However, the National Police's Intelligence Board does not have a legal instrument that underlies the authority to supervise foreigners, based on Act no. 2 of 2022 concerning the National Police and the need for support in the PORA Team system. This research aimed to determine the role and implement strategic planning for the National Police Agency in overcoming various polemics regarding the supervision of foreign journalists in Indonesia as one of the implementations of strategic intelligence studies. The method used is interpretive qualitative with data collection techniques, documentation, and interviews with selected sources by purposive sampling. The data obtained were then analyzed in depth. The role of The Intelligence Board of Polri in supervising foreign journalists have not been maximized and needs to be optimized to maintain National Security. It is necessary to formulate new regulations and revise regulations on the supervision of foreigners, especially foreign journalists, including the criminal aspects of foreign intelligence activities, coordination, communication, and collaboration between ministries/agencies, and the urgency of making a Perpol for the supervision of foreigners, division of tasks and authorities in the supervision of foreigners to improve the quality of the performance of the National Police The Intelligence Board of in carrying out their work.